2001
DOI: 10.1038/eye.2001.15
|View full text |Cite
|
Sign up to set email alerts
|

The acute effect of pilocarpine on pulsatile ocular blood flow in ocular hypertension

Abstract: The acute effect of Conclusion Acute application of pilocarpine 2% drops increased POBF to a significant extent in untreated ocular hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…78 Pilocarpine significantly increased pulsatile ocular blood flow in patients with untreated OHT in one study. 79 In contrast, studies conducted in patients with glaucoma as well as in healthy volunteers found no effect of pilocarpine on the pulsatile component of ocular blood flow. 80,81 There is no study supporting that parasympathomimetics exert any non-IOPrelated neuroprotective effects in glaucoma patients.…”
Section: Topical Therapiesmentioning
confidence: 96%
“…78 Pilocarpine significantly increased pulsatile ocular blood flow in patients with untreated OHT in one study. 79 In contrast, studies conducted in patients with glaucoma as well as in healthy volunteers found no effect of pilocarpine on the pulsatile component of ocular blood flow. 80,81 There is no study supporting that parasympathomimetics exert any non-IOPrelated neuroprotective effects in glaucoma patients.…”
Section: Topical Therapiesmentioning
confidence: 96%
“…The pulsatile component of ocular blood flow is primarily choroidal. 5 It has been clinically applied to investigate in various ocular diseases including glaucoma, 6,7 age-related macular degeneration, 8,9 diabetic retinopathy, 10,11 choroidal melanoma, 12 and retinal pigmentosa. 13 Graves' disease (GD) is an autoimmune disorder characterized by hyperthyroidism, diffuse goitre, ophthalmopathy, and rarely, dermopathy.…”
Section: Introductionmentioning
confidence: 99%
“…A study on human subjects undergoing cardiac catheterization reported that acetylcholine induced vasodilation in normal epicardial coronary arteries, but vasoconstriction in arteries with angiographically evident artherosclerosis. 17 Systemically and topically applied cholinergic agents were reported to increase ocular blood flow in experimental animals 40,41 and humans, 42 suggesting that acetylcholine may be involved in regulation of ocular perfusion by inducing vasodilation via activation of muscarinic receptors. However, as yet, no evidence for abnormal vasoconstriction to acetylcholine has been provided for the ocular circulation in a model of endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%